Peer support and social support in enhancing help-seeking behavior among individuals with suicidal ideation: A systematic review - Lasiono, Lasiono; Retno Lestari; Asti Melani Astari (Jurnal Ilmiah Psikologi Terapan, 2025)
Low help-seeking behaviour among individuals with suicidal ideation is a critical challenge in suicide prevention. One key reason for this reluctance is the stigma surrounding mental health, often reinforced by societal attitudes and misunderstanding. However, growing evidence indicates that peer and social support can significantly improve the likelihood of individuals seeking help. A systematic review was conducted using four academic databases: Science Direct, PubMed, ProQuest, and EBSCO. The review analysed studies published between 2015 and 2024, following the PRISMA method and strict inclusion and exclusion criteria. Out of 7,968 articles initially identified, only 20 met the criteria for final analysis. Findings suggest that both peer and social support play essential roles in encouraging individuals with suicidal thoughts to seek help. When people feel supported, valued, and free from judgment, they are more willing to reach out for assistance. Supportive environments reduce the impact of stigma and foster openness, which is crucial for mental health intervention. In conclusion, enhancing peer and social support systems may lead to improved help-seeking behaviour by creating safe, non-judgemental spaces and promoting mental health literacy. This approach is vital in addressing suicide prevention more effectively.